Self-powered SBD solar-blind photodetector fabricated on the single crystal of β-Ga2O3. Issue 12 (8th February 2018) - Yang, Chao; Liang, Hongwei; Zhang, Zhenzhong; Xia, Xiaochuan; Tao, Pengcheng; Chen, Yuanpeng; Zhang, HeQiu; Shen, Rensheng; Luo, Yingmin; Du, Guotong
Abstract : A Cu SBD solar-blind photodetector was fabricated based on the single crystal β-Ga2 O3 . The device can work at zero bias. Abstract : A Schottky barrier diode (SBD) solar-blind photodetector was fabricated based on the single crystal β-Ga2 O3 . Cu and Ti/Au were deposited on the top and bottom surface of Ga2 O3 as Schottky and ohmic contacts, respectively. The SBD exhibits a higher rectification ratio of up to 5 × 10 7 at ±2 V. The photoresponse spectra show a maximum responsivity at 241 nm and a cutoff wavelength of 256 nm. The solar-blind/ultraviolet and solar-blind/visible rejection ratio can reach a high level of up to 200 and 1000, respectively. It is interesting that the device has a clear response to the solar-blind wavelength at zero bias, which confirms it can be used as a self-powered solar-blind photodetector.